Language Policy and Linguistic Justice Economic, Philosophical and Sociolinguistic Approaches (Springer International Publishing, 2018)
Language policies are increasingly acknowledged as being a necessary component of many decisions taken in the areas of the labor market, education, minority languages, mobility, and social inclusion of migrants. They can affect the democratic control of political organizations, and they can either entrench or reduce inequalities. These are the central topics of this book. Economists, philosophers, political scientists, and sociolinguists discuss - from an interdisciplinary perspective - the distributive socio-economic effects of language policies, their impact on justice and inequality at the national or international level, as well as the connection between language choices and an inclusive access to public services. The range of social and economic issues raised by linguistic diversity in contemporary societies is large, and this requires new approaches to tackle them. This book provides new input to design better, more efficient, and fair language policies in order to manage linguistic diversity in different areas. Topics covered include: theoretical models of linguistic justice and linguistic disadvantage; the assessment of the socio-economic consequences of language policies; the evaluation of the costs, benefits, and degree of inclusion of language planning measures; the politics of migrants' linguistic integration; as well as multilingualism and economic activities. These topics are discussed in different contexts, including the areas inhabited by linguistic minorities, cities receiving migrants, and supranational organizations.